Hydrology model establishment of pit lake: Extreme event rainfall data analysis. Issue 1 (November 2021) - Danasla, M A; Kusuma, G J; Tuheteru, E J; Gautama, R S
Abstract: Analysis of water management in the pit lake is divided into two conditions, namely Continuous Events and Extreme Events. The former is an analysis of pit lake management related to the water filling in a pit lake that takes place continuously. Meanwhile, the later is the analysis of pit lake management related to the possibility of extreme conditions that will occur, including extreme rainfall. This study is focused only on the Extreme Event conditions. The Gumbel method is used to calculate the planned return period rainfall T concerning the prediction of extreme rainfall. Meanwhile, for a certain return period, rainfall intensity can be predicted using the Mononobe formula. Based on the result of calculation the Gumbel method, it shows that the planned rainfall for a return period of 10 years is 132.9 mm / day. Then based on the results of the calculation of rainfall intensity using the Mononobe formula, it is obtained that the intensity of rainfall for a return period of 10 years with a concentration-time of 5 minutes is 241.5 mm/hour, while the amount of rainfall intensity with a concentration-time of 300 minutes or 5 hours is 15.8 mm/hour.